The association between visual exploration and passing performance in high-level U13 and U23 football players. Issue 4 (1st October 2020) - McGuckian, Thomas B.; Beavan, Adam; Mayer, Jan; Chalkley, Daniel; Pepping, Gert-Jan
ABSTRACT: Purpose: The visual exploratory actions (i.e., scanning head movements) used by football players to perceive their surrounding environment have recently gained interest. While this has resulted in important findings relating to visual exploration during natural match-play, often the study designs lacked the experimental control of laboratory-based experimental settings. We aimed to investigate whether visual exploratory action is associated with passing performance for high-level U13 and U23 players in a controlled skill assessment setting. Methods: Fourteen U13 and 13 U23 football players from a Bundesliga club completed a standardised 32-trial sequence in the Footbonaut. Exploratory head movements were recorded with a head-worn inertial sensor, from which the count, frequency and excursion of head movements were extracted before and during ball possession. Ball reception and disposal were coded for each trial, and performance was operationalised as the time taken to complete each trial. Results: Across all players, visual exploratory action was associated with passing performance. The variables that best explained faster performance were 1) a higher number of head turns before receiving the ball, 2) a lower number of head turns when in possession of the ball, and 3) being an U23 player. However, different combinations of variables explained performance for U13 and U23 players. Conclusion: The findings demonstrate the value of scanning before receiving the ball to prospectively control passing actions in the Footbonaut. Future research should investigate the shared and contrasting characteristics of scanning actions, as they are observed by players in skill assessment tasks such as the Footbonaut, during training and during match-play.